ANALISIS RENCANA PELAKSANAAN PEMBELAJARAN TEMATIK KURIKULUM 2013 YANG MENGGUNAKAN MODEL STUDENT TEAMS- ACHIEVEMENT DIVISIONS DI KELAS IV SEKOLAH DASAR - Fitriyani Fitriyani; Siti Halidjah; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research aims to analyze the plan of implementation of thematic learning curriculum 2013 which uses the model of student teams-achievement divisions in grade IV Elementary School 27 Southeast Pontianak. This type of research is qualitative descriptive research. The method used in this study is a descriptive method with a qualitative approach. The subject in this study was Grade IV Teacher A of State Elementary School 27 Southeast Pontianak. The study used primary data sources. The data collection techniques used are documentation techniques and interview techniques, with the data collection tool being the researcher itself while other instruments as support. Data analysis techniques are carried out through four stages, namely data collection, data reduction, data presentation and conclusion drawing. Testing the validity of the data used is triangulation. The results showed that the learning implementation plan made by the Teacher is a part that is already aligned and not yet aligned with the standard components of the Process Of Permendikbud Number 22 year 2016 as well as in the core activities, the planning made by the Teacher already uses the model of student teams-achievement divisions, although there are still steps that are not listed in the learning implementation plan. Keywords: Curriculum 2013, Lesson Plan, Student Teams Achievement Divisions